The Correlation Between Students’ Imperative Sentence Mastery And Their Ability In Writing Procedure Text At MTs Sriwijaya East Lampung - Muhammad Arif Mustaqim (Social Science Studies, 2021)
This research is conducted based on the preliminary research that are many students difficult in writing procedure text. The students are still confused about how to start writing and applying grammar in writing. The objective of the research was to know whether there was a correlation between students’ imperative sentence mastery and their ability in writing procedure text at MTs Sriwijaya East Lampung. This was correlation research. It was used to know the correlation between students’ imperative sentence mastery and their ability in writing procedure text. The population of this research was the students at the MTs Sriwijaya east Lampung of the ninth grade of the first semester. The total sample in this research was 28 students. In collecting data, using 20 multiple choices for imperative sentence test and writing a paragraph for procedure text test. After giving the test, the writer analyzed the data by using SPSS Statistic 17.0 After doing the hypothetical testing, the result demonstrated that there was a positive correlation between students’ imperative sentence mastery and their ability in writing procedure text. Based on the data analysis computed by using SPSS, it was obtained that Sig = 0.004 and α = 0.05. It means that Ha is accepted because Sig ˂ α = 0.05. Based on this research, it was suggested that to have a good writing procedure text, students should have a good mastery of imperative sentences.